Optimization of Cutting Parameters in Drilling of AISI 304 Stainless Steel Using Taguchi and ANOVA. (2016) - Balaji, M.; Murthy, B.S.N.; Rao, N. Mohan
Abstract: The present work deals with the effect of cutting parameters namely cutting speed, feed rate and helix angle on the tool life. The experiments were performed on drilling of AISI304 steel with carbide drill bits. Design of experiments was prepared according to Taguchi orthogonal array of L8 and experiments were performed with two levels of the cutting parameters. The effects of cutting parameters were analyzed by evaluating the amplitude of drill bit vibration and surface roughness. A Laser Doppler Vibrometer (LDV) was used for online data acquisition of drillbit vibration and a high-speed Fast Fourier Transform analyzer is used to process the acousto optic emission (AOE) signals. Taguchi and Analysis of Variance methods were used to identify significant cutting parameters affecting the drill bit vibrations and surface roughness. From the experimental results vibration of drill bit is found to be increased with the progression of the tool wear. Optimum levels of cutting parameters for surface roughness are obtained as 25 degrees of helix angle, 12 mm/min of feed rate and 800 rpm spindle speed. Optimum levels of cutting parameters for acceleration of vibration are obtained as 25 degrees of helix angle, 10 mm/min of feed rate and 600 rpm spindle speed.